Evaluation of Enzyme Immunoassay (EIA), Immunoblot and HIV RNA Polymerase Chain Reaction Test Results in the Diagnosis of Human Immunodeficiency Virus (HIV) Infection - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2019)
Acquired Immunodeficiency syndrome (AIDS) is an important global public health issue. Increasing HIV/AIDS cases reported each year has become a serious health problem for our country. The fourth generation enzyme immunoassay (EIA) test is the first step in the laboratory diagnosis of human immunodeficiency virus (HIV) infection. When the EIA test is repeatedly reactive, antibody-based tests such as immuno blot (IB), line immunoassay (LIA), HIV 1-2 antibody differentiation immunoassay, and HIV RNA tests for the early period of infection are used as confirmatory tests. The aim of this study was to evaluate the results of three different methods for the diagnosis of HIV infection. HIV 1-2 IB and quantitative HIV-1 RNA PCR tests were performed in 199 patient samples. These samples were detected as the reactive or gray zone with HIV 1-2 Ab+Ag EIA test between 2010 and 2015 at Akdeniz University Hospital, Microbiology Laboratory. HIV 1-2 Ab+Ag determination in serum samples was performed with the EIA method (Elecsys HIV combi PT test, Roche Diagnostics, Germany). A commercial kit (INNO-LIA HIV I-II Score, Innogenetics, Belgium) was used for HIV 1-2 IB method. The presence of HIV-1 RNA was investigated by automated nucleic acid extraction and real-time PCR method (Ampliprep/COBAS Tagman HIV-1 Test, Roche Diagnostics, Germany) in plasma samples. For statistical analysis, SPSS, Mann Whitney U test was used, ROC analysis was performed and p< 0.05 value was considered statistically significant. HIV 1-2 Ab+Ag EIA COI (cut-off index) median value was higher with positive HIV 1-2 IB and HIV-1 RNA results than negative HIV 1-2 IB and HIV-1 RNA results. These values were 394 (range: 11.5-2272) and 1.79 (range: 1.01-83.3) respectively and this difference was statistically significant (p< 0.001). HIV-1 RNA test results were positive in one patient with gray zone and two patients with negative HIV 1-2 IB result (viral loads were > 10.000.000, > 10.000.000 and 5.040.000 copies/ml, respectively). For the kit that we used for HIV 1-2 Ab+Ag EIA COI ratio of >16.45 had a sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 97.6%, 98.1%, 97.6% and 98.1%, respectively for the detection of HIV infection (r= 0.994, p< 0.001). HIV 1-2 Ab+Ag EIA S/CO ratio of < 9.26 had a sensitivity, specificity, PPV and NPV of 100%, 92.5%, 91.1% and 100% (p< 0.001). HIV infection is diagnosed if HIV 1-2 Ab+Ag EIA test result is repeatedly reactive and HIV 1-2 IB test and HIV-1 RNA tests are positive. In our study, HIV 1-2 Ab+Ag EIA COI median value was 394 (range: 11.5-2272) in this group of patients (p< 0.001). HIV-1 RNA PCR test was positive in three patients with > 10.000.000, 5.040.000 and > 10.000.000 copies/ml whose EIA tests were repeatedly reactive. HIV IB test was detected as the gray zone in one of them and as negative in the remaining two (HIV EIA S/CO values were 265, 9.5 and 131.8, respectively). These patients were diagnosed as acute HIV infection with clinical and laboratory findings. In conclusion, HIV RNA should also be performed and included in the diagnostic algorithm for acute HIV infection.
Keywords: HIV enzyme immunassay; cut off index; acute HIV infection; FALSE-POSITIVE RATE